Tyrel [videorecording (DVD)] - Silva, Sebastian, 1979-; Silva, Sebastian, 1979-; Silva, Sebastian, 1979-; Mitchell, Jason, 1987-; Zegen, Michael; Abbott, Christopher, 1986- (Magnolia Home Entertainment, 2019)
A man joins his friend on a trip for a weekend birthday party with a bunch of other men he doesn't know and discovers that he is the only black guy in the group.